A dialogical perspective on composition: the classroom responds to gadamer - Peter Sotiriou (Ilha do Desterro)
Composition theory has in the past two decades been informed by three pedagogical movements. The older process pedagogy foregrounds the student writer in the act of composing. In the past decade, reader response theory has spoken to classroom practice in the forms of collaborative learning and writing across the curriculum pedagogics. In both of these pedagogics, the student writer is perceived as an initiate in a specialized community of writers, and her goal is to master the reading and writing conventions that shape the knowledge in that chosen field. Finally, in the pedagogics of E.D. Hirsch and Allan Bloom, there is a focus on determining valid textual meaning: for these theorists, student writers need to learn their culture before they can engage in any meaningful reading and writing.